Ghrelin modulates mesolimbic reactivity to alcohol cues in alcohol-addicted subjects: a functional imaging study - Koopmann, Anne; Bach, Patrick; Schuster, Rilana; Bumb, Jan Malte; Vollstädt-Klein, Sabine; Reinhard, Iris; Rietschel, Marcella; Witt, Stephanie; Kiefer, Falk (Addiction biology, 2019)
Ghrelin has been shown to be involved in the pathophysiology of alcohol dependence, affecting alcohol self-administration and craving. However, the mechanism of action in alcohol dependence still has to be determined. We thus investigated whether ghrelin is associated with mesolimbic cue reactivity to alcohol cues and alcohol craving in recently detoxified alcohol-addicted subjects. We included 41 recently detoxified alcohol-dependent individuals. Functional magnetic resonance imaging (fMRI) was used to study mesolimbic cue reactivity during the presentation of alcohol-related pictures. Additionally, we assessed patients' alcohol craving using the Alcohol Urge Questionnaire and a visual analogue scale. Plasma concentrations of total and acylated (activated) ghrelin were measured in parallel to the fMRI session. The association between ghrelin plasma concentrations, mesolimbic cue reactivity and alcohol craving was assessed by performing correlation and mediation analyses. Alcohol-induced brain response in a network of brain clusters, including the right and left ventral striatum, showed a significant positive association with acylated ghrelin plasma concentration. Additionally, acylated ghrelin was significantly associated with craving. Mediation analyses showed that the association between acylated ghrelin plasma concentration and alcohol craving is mediated by a cue-induced brain response in the ventral striatum. Based on the finding that ghrelin modulates mesolimbic reactivity to alcohol cues, the following should be considered: If alcohol craving and the appetitive status were interrelated, this has to be taken into account when implementing fMRI studies for addictive disorders. Moreover, appetite regulation seems to represent a valid treatment target for reducing cue reactivity in addictive disorders.